2015
DOI: 10.1007/s00606-015-1229-7
|View full text |Cite
|
Sign up to set email alerts
|

SEM investigation of pollen from the lower Eocene (Carinthia and Salzburg in Austria and Brixton, London area, in England): new findings of Vitaceae, Euphorbiaceae, Phyllanthaceae, Fabaceae, Anacardiaceae, Araliaceae and Apiaceae

Abstract: Three European lower Eocene localities comprising sediments from the Paleocene-Eocene Temperature Maximum (PETM, St Pankraz, Austria and Brixton, England) and the Early Eocene Climate Optimum (EECO, Krappfeld, Austria) have been investigated palynologically with light microscopy and scanning electron microscopy. The pollen taxa systematically investigated here have been affiliated to the following families and genera: Vitaceae gen. indet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…Major range shifts to southern latitudes and local extinctions at higher latitudes are likely to have occurred during cool periods and may have enabled the Neotropics colonization in parallel with northern latitude extinctions. The fact that the most reliable fossil of the Asian Palmate group is from the Eocene of Tennessee (Dilcher & Dolph, ; Dilcher & Lott, ) together with the existence of other putatively Asian Palmate fossils from the Eocene of Europe (Hofmann et al, ) and eastern North America (MacGinitie, ), supports the extinction scenario at the northern latitudes.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Major range shifts to southern latitudes and local extinctions at higher latitudes are likely to have occurred during cool periods and may have enabled the Neotropics colonization in parallel with northern latitude extinctions. The fact that the most reliable fossil of the Asian Palmate group is from the Eocene of Tennessee (Dilcher & Dolph, ; Dilcher & Lott, ) together with the existence of other putatively Asian Palmate fossils from the Eocene of Europe (Hofmann et al, ) and eastern North America (MacGinitie, ), supports the extinction scenario at the northern latitudes.…”
Section: Discussionmentioning
confidence: 86%
“…Dispersal‐extinction‐cladogenesis seems to be more appropriate for the reconstruction of the biogeographic history of plants with long‐distance dispersal syndromes, as the Asian Palmate group, because it allows for persistence of widespread descendants from widespread ancestors while DIVALIKE forces to geographic speciation event after the divergence of a widespread ancestor. Also, intercontinental widespread distribution is not only observed for certain generic lineages nowadays ( Hedera, Oplopanax ) but also in the past as inferred from paleobotanical evidence ( Dendropanax : North America‐Tennessee, 53–52 Mya, Dilcher & Dolph, ; Wilf, ; Dilcher & Lott, ; Wyoming, 46.2–40.4 Mya, MacGinitie, ; and Europe–England, 59.2–56, Hofmann et al, ; Oreopanax : North America‐Colorado, 55.8–33.9 Ma, MacGinitie, ; and South America‐Argentina, 55.8–5.3 Ma, Berry, ). The amphi‐Pacific spatial frame indicated by DEC places the radiation of the core in a completely different scenario from the one described in Valcárcel et al ().…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The Apiaceae contain over 3700 living species and include several important crops, yet their fossil record is sparse and poorly understood (e.g., Friis & al., ; Banasiak & al., ). Apiaceae fossil pollen are known since as early as the Cretaceous (Banasiak & al., and references therein), but the identification below family rank was seldom attempted (e.g., Gruas‐Cavagnetto & Cerceau‐Larrival, ) due to morphological similarities among genera (Hofmann & al., ). Putative Apiaceae macrofossil fruits (mericarps) like Carpites ulmiformis Dorf are also known from the Cretaceous, although their taxonomical affinities are not completely resolved (Manchester & O'Leary, ).…”
Section: Discussionmentioning
confidence: 97%
“…Affinity. Hofmann et al (2015) suggested that this pollen type might belong to Euphorbiaceae or Phyllanthaceae because of the striae and rudimentary honeycomb pattern and the small circular endoporus. Other suggestions include Sapindaceae (Tschudy 1973) or Anacardiaceae based on morphological similarities with Rhoipites (Harrington 2003).…”
Section: Systematic Paleontologymentioning
confidence: 99%